Maternal effect of agronomic and morphological characters on cluster structure of F3 soybean lines - PANJI HANDOKO BADIARAJA; Siti Zubaidah; HERU KUSWANTORO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Badiaraja PH, Zubaidah S, Kuswantoro H. 2021. Maternal effect of agronomic and morphological characters on cluster structure of F3 soybean lines. Biodiversitas 22: 969-982. The study was to determine the maternal effect on the agronomic and morphological characters and their impact on F3 soybean lines cluster structure. The results showed the maternal effect was found in agronomic and morphological characters. In agronomic characters, the maternal effect was shown by plant height, number of productive nodes, number of filled pods, seed weight per plant, and 100-seed weight. In morphological characters, pod width, pod thickness, seed width, and seed thickness were shown by pod width. Based on cluster analysis results, at Grobogan/UM 3-2 cross, the best individuals for the number of branches, the number of productive nodes, the number of filled pods, the number of unfilled pods, the number of seeds per plant, and the seed yield per plant were obtained in Cluster 2. For the 100-seed weight, pod length, pod width, pod thickness, seed width, and seed thickness, the best individuals were in Cluster 1. Meanwhile, at UM 3-2/Grobogan cross, the best individuals for the plant height were in Cluster 2, while seed length was in Cluster 3. For the number of seeds per pod, the best individuals can be obtained from Cluster 6. The maternal-effect led to the cluster structure differed between cross and its reciprocal.